Clinico-Therapeutic Management of Reticular Abscess due to Ruminal Acidosis in Jaffarabadi Buffalo – A Report of Four Cases - N Parmar, Jagruti; L Parmar, Vijay; G Dodia, Piyushkumar; V Mavadiya, Suresh; K Bilwal, Avinash; A Vagh, Arshi (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Reticular abscesses in buffaloes are a frequent complication  of traumatic reticuloperitonitis or foreign body syndrome,  primarily caused by the anatomical structure and function  of the reticulum (Athar et al., 2010). These abscesses often  result from foreign body penetration or bacterial infections,  causing severe inflammation that can lead to toxaemia and  heart failure if left untreated (Abu-Seida and Al-Abbadi, 2016).  In addition to trauma, prolonged ruminal acidosis, often due  to improper dietary management, is a significant contributing  factor (Sharma et al., 2015). When ruminants consume high  amounts of rapidly fermentable carbohydrates, such as  grains, subacute ruminal acidosis (SARA) can occur, leading  to a drop in ruminal pH and weakening of the rumen and  reticulum walls, making them more susceptible to bacterial  infections and abscess formation (Caldwell et al., 2011). This  study documents the clinico-therapeutic management of  reticular abscesses due to ruminal acidosis in Jaffarabadi  buffaloes.
Keywords: management; consume; decreased milk yield; haematological analysis; guidance